Anaesthesia-related complications in patients with Down syndrome: A cross-sectional study from Tripoli-Libya (Comprehensive Journal of Science, 2025)
Patients with Down syndrome present unique challenges during generalanesthesia due to their anatomical and physiological characteristics. This cross-sectional studyinvestigates the rate and nature of anesthesia-related complications in 30 Down syndromepatients across three hospitals in Tripoli-Libya. The findings reveal high rates of congenitalheart defects (70%), intraoperative awareness (66.7%), and intubation difficulties (43.3%).Sevoflurane and propofol were the most commonly used anesthetic agents. The studyhighlights the need for specific anesthesia protocols and enhanced preoperative assessment toreduce risks in this vulnerable population
Keywords: : Down syndrome, anesthetic complications, congenital heart defects, intraoperative awareness, Libya